Um estudo cenográfico da “ciência” divulgada na revista Pesquisa FAPESP - Delege, Marina (Universidade Federal de São Carlos, 2019)
This research investigates the meanings attributed to the word “science” in discourses of scientific divulgation the way it is built on an important communication device: Pesquisa FAPESP magazine. It is seen, here, as a mídium (DEBRAY, 2000): a vector and value that allows to identify one formative matrix, the FAPESP – Foundation of support to research of São Paulo state, because it is an editorial object tailored for results communication obtained by one of the largest research sponsoring agencies of Brazil, as it mobilizes 1% of the state of São Paulo’s tax revenue per year and e.g. disbursed R$1,058 billion for supporting 24.026 research projects in 2017, according to the activities report published by FAPESP in edition n. 270 on August 2018. Our corpus is constituted by the first 270 editions published, which includes all editions published between August 1995 and August 2018. To employ a descriptive listing of all editions aiming to map the genesis of such discourse, looking after meanings attributed to the word “science” present in scientific divulgation done by Pesquisa FAPESP magazine, we used the theoretical precepts of French Discourse Analysis as foundations, specifically the theory of enunciation scenes proposed by Maingueneau (2008a), which contributes towards comprehending of textualized discoursivization on Pesquisa FAPESP magazine, since it approaches the textual surface in which the discursive regime employ its values and powers.
Keywords: Ciência; Cenas da enunciação; Mídium; Revista Pesquisa FAPESP; Science; Enunciation scenes; Pesquisa FAPESP magazine; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA